2010
DOI: 10.3201/eid1607.100106
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus gattiiGenotype VGIIa Infection in Man, Japan, 2007

Abstract: We report a patient in Japan infected with Cryptococcus gattii genotype VGIIa who had no recent history of travel to disease-endemic areas. This strain was identical to the Vancouver Island outbreak strain R265. Our results suggest that this virulent strain has spread to regions outside North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 14 publications
1
41
0
Order By: Relevance
“…Given that VGII is the predominant molecular type (VGI is uncommon) in north/northeastern Brazil but not in the southern part of the country, those authors postulated that the ecological niche of this genotype may be expanding (223). Support for the notion that the niche of the VGII genotype is evolving is the observation of infection caused by molecular type VGIIa in a Japanese patient in Tokyo with no history of travel to an area of known endemicity; VGIIa genotype strains have not previously been documented in Japan (249). Further environmental surveillance is needed to determine new reservoirs of C. gattii.…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 78%
See 2 more Smart Citations
“…Given that VGII is the predominant molecular type (VGI is uncommon) in north/northeastern Brazil but not in the southern part of the country, those authors postulated that the ecological niche of this genotype may be expanding (223). Support for the notion that the niche of the VGII genotype is evolving is the observation of infection caused by molecular type VGIIa in a Japanese patient in Tokyo with no history of travel to an area of known endemicity; VGIIa genotype strains have not previously been documented in Japan (249). Further environmental surveillance is needed to determine new reservoirs of C. gattii.…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 78%
“…Single cases of infection have also been reported in the United States, including New England (85,243,247), New Mexico (272), and Florida (253); Europe (91,95,106,245); Asia, including Japan and Singapore (227,246,249); and South America (223,256). Most recently, Harris et al reported 25 cases, inclusive of previously described patients (247,253) diagnosed between 2009 and 2012, from Montana, Alabama, California, Hawaii, and Michigan; none of these patients had traveled to areas of C. gattii endemicity (251).…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the first case report of a patient in Japan infected with Cr. gattii genotype VGIIa noted that the patient had no recent history of travel to any disease endemic areas (40), suggesting that the virulent strain may have spread to regions outside North America. Cr.…”
Section: Discussionmentioning
confidence: 98%
“…It occurs occasionally to AIDS patients that they get opportunistic infection of pathogenic bacteria, especially tuberculosis infection of Candida albidus, Mycobacterium co-infected with tuberculosis, Escherichia coli, G Klebsiella, Pseudomonas aeruginosa bacteria and so on [1]- [4]. In the Cryptococcus, Cryptococcus neoformans is the main, but Cryptococcus albicans is rare.…”
Section: Introductionmentioning
confidence: 99%